A Review of Enrico Moretti's The New Geography of Jobs - Glaeser, Edward (Journal of Economic Literature, 2013)
Why is prosperity distributed so unevenly across America's metropolitan areas? While population growth has gone disproportionately towards the Sunbelt, high-skill areas have experienced the strongest income growth since 1970. Gaps between more and less educated areas were modest forty years ago, but they have become quite large, and far larger than would be predicted solely by the general rise in the returns to skill. Unemployment rates during the recent recession were also strongly correlated with area level education. This essay reviews Enrico Moretti's The New Geography of Jobs, which both describes and explains these significant regional trends. (JEL I32, J24, R12, R23, R32)